Acute haemodynamic changes after percutaneous mitral valve repair: relation to mid-term outcomes. Issue 2 (7th October 2011) - Gaemperli, Oliver; Moccetti, Marco; Surder, Daniel; Biaggi, Patric; Hurlimann, David; Kretschmar, Oliver; Buehler, Ines; Bettex, Dominique; Felix, Christian; Luscher, Thomas F; Falk, Volkmar; Grunenfelder, Jurg; et al.
Abstract : Background: Percutaneous mitral valve repair (MVR) using the Evalve MitraClip has been recently introduced as a potential alternative to surgical MVR. Objective: To assess immediate haemodynamic changes after percutaneous MVR using right heart catheterisation. Design: Single-centre longitudinal cohort study. Setting: Tertiary referral centre. Patients: Fifty consecutive non-surgical patients (age 74±14 years, EuroSCORE 26±14) with moderate to severe (3+) and severe (4+) mitral regurgitation (MR) due to functional (56%), degenerative (30%) or mixed (14%) disease were selected. Interventions: MitraClip implantation was performed under general anaesthesia with fluoroscopy and echocardiographic guidance. Haemodynamic variables were obtained before and after MVR using standard right heart catheterisation and oximetry. Main outcome measures: Haemodynamic changes immediately before and after MVR. Results: Acute procedural success (reduction in MR to grade 2+ or less) was achieved in 46 (92%) patients. Mitral valve clipping reduced mean pulmonary capillary wedge pressure (mPCWP) (from 17±7 to 12±5 mm Hg), PCWP v-wave (from 24±11 to 16±7 mm Hg) and mean pulmonary artery pressure (mPAP) (from 29±12 to 24±6 mm Hg), and increased the cardiac index (CI) (from 3.1±1.0 to 3.9±1.1 l/min/m 2 ) (all p<0.05). On Cox univariate regression analysis, mPCWP, PCWP v-wave- and mPAP-changes were associated with death, open-heart surgery for MR and/or hospitalisation for heart failure on follow-up. Conclusion: In a heterogeneous population with predominantly functional MR, percutaneous MVR with the Evalve MitraClip system lowers mPCWP, PCWP v-wave and mPAP by 20%, 20% and 8%, respectively, and increases the CI by 32%.